Countering Pharmaceutical Fraud: Analyzing Pharmacist Competence and Policy Interventions in Falsified Medicines in Shymkent (Bangladesh Journal of Medical Science, 2025)
Background Falsified medicines pose a severe threat to global healthcare, contributing to treatment failures, adverse health outcomes, and economic burdens. Aims This study aims to assess the awareness, detection capabilities, and reporting behaviors of pharmacists in Shymkent, Kazakhstan, regarding falsified medicines. Method A mixed-methods approach was used, incorporating a quantitative survey of 250 pharmacists and qualitative interviews with industry professionals. Data were analyzed using descriptive statistics, thematic analysis, and inferential statistical methods. The findings indicate that weight-loss medications are the most frequently falsified drugs in Shymkent, followed by erectile dysfunction drugs, weight-loss medications, and antibiotics. Most pharmacists relied on visual inspection to identify falsified medicines, but only 31% reported using formal reporting mechanisms, such as the Yellow Card Scheme. Notably, 72.8% of pharmacists actively reported cases of falsified medicines, yet many expressed uncertainty about detection techniques. A significant proportion of respondents lacked formal training in falsified medicine identification, and over half (51.6%) showed reluctance to participate in future training programs. Results This study highlights critical gaps in pharmacist training and regulatory enforcement, emphasizing the need for advanced detection technologies, enhanced regulatory cooperation, and pharmacist education initiatives. Strengthening the role of pharmacists in early detection and reporting, combined with the implementation of AI-driven verification systems and blockchain tracking, could significantly reduce the circulation of falsified medicines. Conclusion Future policies should focus on cross-border collaboration, stricter legal frameworks, and investment in pharmacist training to safeguard public health.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 514-525